Hip disorders and spinopelvic alignment: a current literature review - Toshiyuki Tateiwa; Tsunehito Ishida; Takuya Kusakabe; Toshinori Masaoka; Kenji Endo; Takaaki Shishido; Yasuhito Takahashi; Kengo Yamamoto (Journal of Joint Surgery and Research, 2023)
Purpose: The importance of considering the influence of spinal alignment on the pathology of the hip joint has been widely accepted. The primary objective of this study is to give a comprehensive view of recent findings on the influence of sagittal spinopelvic alignment on hip osteoarthritis (HOA) and total hip arthroplasty (THA). Methods: An English-language literature search was performed with PubMed and Medline databases to identify peer-reviewed studies published within the last 5 years (2017–2022) on the topic of hip disorders and spinopelvic alignment. Results and conclusions: It was reported that the risk of developing primary HOA may increase in patients with high sacral slope (SS) and low pelvic tilt (PT), whereas that of secondary HOA based on acetabular dysplasia (AD) may increase in patients with high lumbar lordosis (LL), SS, and pelvic incidence (PI). In addition, surgeons need to consider that the hip–spine motion may change from the preoperative one owing to changes in some spinopelvic parameters following THA. However, the significance of these changes is not consistent across the studies. Since low PI, PI-LL mismatch, and low SS during sitting and standing may contribute to the risk of prosthetic impingement followed by dislocation, great care should be taken regarding the loss of spinopelvic mobility after spinal fusion surgery.